Stalking Strain, Concurrent Negative Emotions, and Legitimate Coping Strategies: A Preliminary Test of Gendered Strain Theory - Ngo, Fawn T. (American journal of criminal justice, 2013)
Using data from the Supplemental Victimization Survey of the NCVS and relying on theoretical direction provided by Broidy and Agnew’s gendered strain theory, we examine gender differences in the concurrent emotional responses to a type of strain that has not been examined by GST researchers: stalking. In particular, we assess whether males and females experience similar levels of concurrent negative emotions and whether concurrent negative emotions are similarly associated with legitimate coping resources for males and females. We found the co-occurrence of emotions is more typical among females than males and the impact of concurrent emotions on the strain/non-crime relationship appear to affect females more than males. One notable finding that emerged from our results is that the co-occurrence of emotions can have both proscriptive and precipitating effects on legitimate outcomes. The implications of our findings for theorists and researchers are also discussed.